O papel do gestor hospitalar e dos centros de convivência do idoso na promoção de um envelhecimento saudável - SILVA, Emerson Gregório da; SOUSA, Gisele Alves de (298, 2024)
O envelhecimento humano é um processo gradual e irreversível, que se torna cada vez mais relevante devido ao aumento da expectativa de vida. A Organização Pan-Americana da Saúde (OPAS) destaca a importância do planejamento nos serviços de saúde para prevenir doenças comuns entre os idosos, como câncer e diabetes. A inserção em grupos de convivência, especialmente nos Centros de Convivência do Idoso (CCI), é uma estratégia fundamental ´para combater a exclusão e promover a socialização, contribuindo para a saúde e autoestima dos idosos. A expectativa de vida no Brasil aumentou significativamente, passando de 45 anos em 1940 para 76 anos em 2020, refletindo melhorias nas condições de saúde e políticas públicas. O envelhecimento ativo é promovido pela Organização Mundial da Saúde (OMS) como uma forma de garantir que a longevidade seja acompanhada pela qualidade de vida. Desde a década de 1990, políticas públicas como a política Nacional do Idoso e o Estatuto do Idoso têm sido inovadoras para garantir os direitos e a dignidade dos idosos. O programa “São Paulo Amigo do Idoso” busca garantir os direitos e promover a inclusão social dos idosos por meio de ações em saúde, educação e lazer, incluindo os CCIs, que oferecem um espaço seguro para atividades sociais e recreativas. O papel do gestor hospitalar é essencial nesse contexto, pois deve planejar e integrar serviços voltados ao envelhecimento saudável, promovendo a prevenção, capacitação da equipe de saúde e autonomia dos idosos. Os gestores podem desenvolver estratégias que considerem as especificações da população idosa, integrando diferentes níveis de atendimento à saúde e promovendo práticas preventivas, educativas e inclusivas. A capacitação contínua da equipe de saúde e o envolvimento da comunidade são essenciais para garantir um atendimento qualificado e distintivo. Concluindo que uma gestão eficaz, aliada a políticas públicas robustas e à promoção da convivência social nos CCIs, é necessário para garantir um envelhecimento digno e saudável no Brasil.

Human aging is a gradual and irreversible process that is becoming increasingly important as life expectancy increases. The Pan American Health Organization (PAHO) emphasizes the importance of planning health services to prevent diseases common among the elderly, such as câncer and diabetes. Inclusion in social groups, especially in Centros de Convivência do Idoso (CCI), is a fundamental strategy to combat exclusion and promote socialization, contributing to the health and self-esteem of the elderly. Life expectancy in Brazil has increased signicantly, from 45 years in 1940 to 76 years in 2020, reflecting improvements in health conditions and public policies. Active aging is promoted by the Wolrd Health Organization (WHO) as a way to ensure that longevity is accompanied by quality of life. Since the 19900s, public policies such as the National Policy for the elderly and the Statute of the Elderly have been innovative in guaranteeing the rights and dignity of the elderly. The “São Paulo Friend of the Elderly” program seeks to guarantee the rights and promote the social inclusion of the elderly through actions in the áreas of health, education and leisure, incluiding the CCIs, which provide a sfe space for social and recreational activities. The role of the hospital manger is essential in this contest, as he or she must plan and integrate services aimed at healthy aging, promoting prevention, health team training and the autonomy of the elderly. Managers can develop strategies that take into account the specifications of the elderly population, integrate diferente levels of health care, and promote preventive, educational, and inclusive practices. Continuous training of the health care. In conclusion, effective mangementemanagement, allied to robust piblic policies and the promotion of social interaction in CCIs, is necessary dignified and healthy ageing in Brazil.

Human aging is a gradual and irreversible process that is becoming increasingly important as life expectancy increases. The Pan American Health Organization (PAHO) emphasizes the importance of planning health services to prevent diseases common among the elderly, such as câncer and diabetes. Inclusion in social groups, especially in Centros de Convivência do Idoso (CCI), is a fundamental strategy to combat exclusion and promote socialization, contributing to the health and self-esteem of the elderly. Life expectancy in Brazil has increased signicantly, from 45 years in 1940 to 76 years in 2020, reflecting improvements in health conditions and public policies. Active aging is promoted by the Wolrd Health Organization (WHO) as a way to ensure that longevity is accompanied by quality of life. Since the 19900s, public policies such as the National Policy for the elderly and the Statute of the Elderly have been innovative in guaranteeing the rights and dignity of the elderly. The “São Paulo Friend of the Elderly” program seeks to guarantee the rights and promote the social inclusion of the elderly through actions in the áreas of health, education and leisure, incluiding the CCIs, which provide a sfe space for social and recreational activities. The role of the hospital manger is essential in this contest, as he or she must plan and integrate services aimed at healthy aging, promoting prevention, health team training and the autonomy of the elderly. Managers can develop strategies that take into account the specifications of the elderly population, integrate diferente levels of health care, and promote preventive, educational, and inclusive practices. Continuous training of the health care. In conclusion, effective mangementemanagement, allied to robust piblic policies and the promotion of social interaction in CCIs, is necessary dignified and healthy ageing in Brazil.
Keywords: Idosos; Envelhecimento; Administração em saúde pública; Política de saúde; Ambiente e Saúde